PENDAPATAN DAN MOTIVASI MASYARAKAT BERBURU RUSA SAMBAR ( Cervus unicolor, Brookei ) - Dian, Rahmad; Muin, Sudirman; anto, Eri (Universitas Tanjungpura, 2014)
The research aims to look at how much revenue from the hunting community actual sambar deer (Cervus unicolor, Brookei) and factors that affect people hunting sambar deer. The method used is the method descriptive with survey forms through interview techniques. Analysis of the data using two types of analysis, namely the descriptive to see income from the hunt sambar deer, the inferential analysis using the test - T (Paired samples T test) and multiple linear regression.There are differences in the actual income from the hunt sambar deer (Cervus unicolor, Brookei ) with earnings beyond sambar deer hunting. Test Results - t two variables ( Paired sample T-test ) there was significant difference between sambar deer hunting revenue swith arnings beyond sambar deer hunting. Chikuadarat test showed there was no significant difference in the level of motivation of the sambar deer hunt. Results showed linear statistical calculations 2 (three) independent variables affect the motivation of the sambar deer hunting community, accessibility (X3) and the level of know ledge (X4). Where as other variables did not affect the motivation of people like the sambar deer hunting income variable (X1), employment opportunities (X2), cosmopolitan (X5), hunting experience (X6), andage (X7). Keyword : Income, factors that affect motivation, Sambar deer (Cervus unicolor, Brookei)